Investigação de mudanças na qualidade das águas subterrâneas do Baixo Acaraú em decorrência do manejo da irrigação - Luna, Nayara Rochelli de Sousa (2012)
Irrigation is currently an important component in the development of agriculture, not only in arid and semiarid regions, but also in other regions, providing the balance of production and avoiding the possible interference caused by the occasional lack of water. Irrigated agriculture has increased the productivity of crops, but the return flows of irrigation are a main contributor in the degradation of water resources (surface and groundwater). This research was conducted aiming to identify the inference of irrigation management and climate seasonality in soil and water resources of form a quantitative and qualitative of Irrigation District Baixo Acaraú – DIBAU, Ceará. The study was conducted with data from water collected in nine shallow wells, six (6) inserted in the irrigated area and three (3) outside irrigated area of DIBAU. Water samples were collected monthly during the August/10 July/11, totaling 12 sampling campaigns. The chemical analyses were performed at the Laboratory of Soil and Water Embrapa agribusiness Tropical. The attributes analyzed in the water were: pH, electrical conductivity (EC), Ca2+, Mg2+, Na+, K+, HCO3 -, Cl-, NH4 +, NO3 - and Sodium Adsorption Ratio (SAR). Soil samples were taken in (2) points, one batch area irrigated and the other in an uncultivated area. Both samples were collected the dry and rainy periods, each 50 cm depth from the surface to the zone of saturation of water table. To check the similarity of water quality was employed the statistical technique of multivariate analysis (cluster analysis) processed in SPSS 16.0. The classification of the chemical quality of water was performed by using the Piper diagram software QUALIGRAF (FUNCEME, 2009). According to the results of the water wells investigated were grouped without presenting geographical continuity, forming two distinct groups for the two seasons. The highest values of cations (Ca2+, Mg2+, Na+ and K+) were recorded in the waters of wells P1, P8 and P9. The soil texture was the determining factor for the reduction of sodium, chloride and nitrate in the soil profile of irrigated area according to the deeper layers. There was an increase in levels of nitrate in water from wells affected by agricultural practices (P5 and P7). These concentrations exceeded the maximum allowed limits by Resolution 357/2005 and by Ordinance 518/2004 for human consumption in certain months of collected. Groundwater the DIBAU were predominantly classified as chlorinated sodium.